Examining the impact of different re-warm-up strategies on non-starter basketball players` physical performance - Flórez-Gil, E.; Mateus, N.; Sampaio, J.; Abade, E. (Journal of Sports Sciences, 2025)
This study assessed the effectiveness of re-warm-up strategies in counteracting performance declines in non-starter female basketball players during prolonged inactivity. Fifteen elite youth players (16.7 ± 0.6 years) participated in a crossover study comparing four re-warm-up protocols following a standardized warm-up. Performance was measured immediately after warm-up and 15-min post re-warm-up using the counter-movement jump (CMJ), drop jump (DJ), and 5-0-5 change of direction test (CODs). Prolonged inactivity (CON) significantly decreased CMJ and DJ height (p < 0.001) and slowed CODs times (p = 0.019). Plyometric re-warm-up (PLY) preserved CMJ, DJ, and CODs performance (p > 0.05), while dynamic stretching (DYN) and passive heat maintenance (TOW) maintained DJ and CODs (p > 0.05) but reduced CMJ (p < 0.001). ANCOVA revealed a significant effect of re-warm-up strategies on CMJ (F = 20.71, p < 0.001, np2 = 0.54), with post hoc tests showing PLY was superior to other protocols (p < 0.001). These findings emphasize the effectiveness of plyometric strategies in maintaining physical performance during inactivity. Tailored protocols considering individual needs and basketball-specific demands can enhance player readiness and team success.